2018
DOI: 10.1111/ijlh.12796
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating microparticles in women with preeclampsia

Abstract: Determining the MP level, especially that of EMPs and LMPs, by a specificity-verified method may reflect the endothelial dysfunction and inflammation involved in PE pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
0
12
0
3
Order By: Relevance
“…In contrast, the positive association between WbcMVs generation and plaque formation in atherosclerosis, as well as their sharp elevation in septic shock, suggest their utility as possible disease biomarkers. Finally, they also seem to have a role on endothelium homeostasis or dysfunction related to breathing disorders and to the increased cardiovascular risk associated with the obstructive sleep apnea (OSA) and pre-eclampsia [ 122 , 123 , 124 , 125 ] ( Table 1 ).…”
Section: White Blood Cell-derived Vesiclesmentioning
confidence: 99%
“…In contrast, the positive association between WbcMVs generation and plaque formation in atherosclerosis, as well as their sharp elevation in septic shock, suggest their utility as possible disease biomarkers. Finally, they also seem to have a role on endothelium homeostasis or dysfunction related to breathing disorders and to the increased cardiovascular risk associated with the obstructive sleep apnea (OSA) and pre-eclampsia [ 122 , 123 , 124 , 125 ] ( Table 1 ).…”
Section: White Blood Cell-derived Vesiclesmentioning
confidence: 99%
“…Four subgroups were divided based on the cell membrane makers. Nine studies reported CD31-marked EMPs 6,8,10,14,15,17,19,27,28 , three studies reported CD62E-marked EMPs 12,15,27 , two studies reported CD144-marked EMPs 17,30 and two studies reported CD51-marked EMPs 16,29 . The pooled concentrations of CD31-marked EMPs were significantly elevated in PE patients (SMD: 2.37, 95% CI: 1.60 to 3.13, I 2 =95%, P < 0.00001), whereas CD62E-marked, CD144-marked and CD51-marked EMPs showed no significant difference [CD62E-marked EMPs (SMD: 0.67, 95% CI: -0.29 to 1.63, I 2 =89%, P = 0.17); CD144-marked EMPs (SMD: -0.37, 95% CI: -1.34 to 0.61, I 2 =75%, P = 0.46); CD51-marked EMPs (SMD: -0.30, 95% CI: -0.71 to 0.10, I 2 =0%, P = 0.15)] between PE and healthy pregnant patients (Figure 4).…”
Section: Empsmentioning
confidence: 99%
“…Nine studies 6,10,12,16,17,25,[28][29][30] reported PMPs in the third trimester. There was no significant difference between PE and healthy pregnant patients (SMD: -0.20, 95% CI: -0.54 to 0.15, I 2 =75%, P = 0.27).…”
Section: Pmpsmentioning
confidence: 99%
See 1 more Smart Citation
“…PE is also associated with hypercoagulability, endothelial dysfunction, and inflammation, resulting in microparticles (MPs) in which microparticles of platelets (PMPs), endothelial cells (EMPs), and leukocytes (LMPs) which are a method of knowing the presence of endothelial dysfunction and inflammation involved in the pathogenesis of PE [147]. Glomerular damage kidneys are common in PE and can be identified with tubular channels such as 1-microglobulin (A1M), retinol-binding protein (RBP), molecule-1 (KIM1), C5b-9, metalloproteinase-2 (TIMP-2), and insulin growth factors binding protein-7 (IGFBP-7) [148].…”
Section: Kidney Disease In Pementioning
confidence: 99%